Parental Communication as a Protective Factor Against Adolescent Risky Sexual Behavior: A Meta-Analysis - Joko Tri Atmojo; Anggun Fitri Handayani; Aris Widiyanto; Ahmad Syauqi Mubarok; Hakim Anasulfalah; Trisakti Halimah Delimasari (Journal of Health Promotion and Behavior, 2025)
Background: Adolescence is a significant developmental stage marked by notable physical, psychological, and social changes. Adolescent reproductive health surveys show that a number of teenagers report engaging in premarital sexual intercourse without fully understanding its social and health consequences. Given this phenomenon, it is crucial to understand the factors that can protect them from risky sexual behaviors, particularly starting from the family. This study aimed to estimate the impact of family communication on risky sexual behavior in adolescents. Subjects and Method: This research is a meta-analysis and systematic review using the PRISMA diagram with PICO frame work (P= adolescent; I = parental communication; C= no parental communication; O= risky sexual behavior). Primary studies were searched through several indexing databases, including PubMed, Google Scholar, and ScienceDirect. Keywords used to facilitate the search for articles include: “parental participation,” or “parental communication,” or “family interaction,” or “sexual risk” or “sexual risk behavior” AND “adults” or “adolescents.” The inclusion criteria for this study are articles published using a cross-sectional study design up to 2024. The statistical analysis used in this study was conducted using the RevMan 5.4 meta-analysis program with both fixed effect and random effect approaches to present the data in the form of forest plots and funnel plots. Results: A total 9 Articles were included in the meta-analysis. The results of the study show that adolescents with low family participation in sexual education, or in the absence of parental communication, are 1.46 times more likely to engage in risky sexual behavior compared to adolescents who receive sexual education or have parental communication, and this result is statistically significant (aOR= 1.46; CI 95%= 1.43 to 1.49; p<0.001). Conclusion: adolescents with low family participation in sexual education, or in the absence of parental communication are more likely to engage in risky sexual behavior compared to adolescents who receive sexual education or have parental communication.